Relationship between dynamic changes of microorganisms in Qupi and the quality formation of Fengxiangxing Huairang Daqu - Cao, Dan; Lv, Jiali; Chu, Jingying; Xu, Shuangshuang; Jin, Chengyong; Zhang, Yongli; Zhang, Yuhang; Zhang, Wen; Kang, Jie (Frontiers in Microbiology, 2024)
In this study, the relationship between the formation of Fengxiangxing Huairang Daqu (FHD) quality and the changes in microflora structure, sensory characteristics, fermentation characteristics, and flavor substances during the forming FHD from Qupi was revealed through microscopic characterization, PacBio SMRT sequencing, and HS-SPME-GC-MS volatile metabolite analysis. The results showed that the 12th day of the culture was the most critical process point, highlighting the most significant differences in microbial community structure, sensory characteristics, fermentation characteristics, and flavor substances. Bacillus licheniformis (43.25%), Saccharopolyspora rectivirgula (35.05%), Thermoascus aurantiacus (76.51%), Aspergillus amstelodami (10.81%), and Saccharomycopsis fibuligera (8.88%) were the dominant species in FHD. S. fibuligera, A. amstelodami, and T. aurantiacus were associated with the snow-white color of the FHD epidermis, the yellow color of the interior, and the gray-white color, respectively. The abundance of T. aurantiacus, A. amstelodami, B. licheniformis, and S. rectivirgula was positively associated with the esterifying power and liquefying power of FHD. The abundance of T. aurantiacus and A. amstelodami was positively correlated with the saccharifying power of FHD. The abundance of S. fibuligera was positively related to the fermenting power of FHD. A total of 248 volatiles were detected in Qupi, mainly including alcohols, esters, aldehydes, and ketones. Of them, eleven volatiles had a significant effect on the flavor of Qupi, such as 1-butanol-3-methyl-, hydrazinecarboxamide, ethanol, phenylethyl alcohol, ethyl acetate, 2-octanone, 1-octen-3-ol, formic acid-hexyl ester, (E)-2-octen-1-ol, ethyl hexanoate, and 2(3H)-furanone-dihydro-5-pentyl-. The abundance of B. licheniformis, S. rectivirgula, T. aurantiacus, and S. fibuligera was positively correlated with the alcohols, aromatic compounds, and phenols in FHD. The abundance of S. fibuligera was positively correlated with the acids, esters, and hydrocarbons in FHD. Overall, these results indicate important theoretical basis and technical support for controllable adjustment of FHD microbial community structure, stable control of FHD quality, and precise, effective, and large-scale guidance of FHD production.